2013
DOI: 10.1111/j.1540-6520.2011.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Counterfactual Thinking and Entrepreneurial Self–Efficacy: The Moderating Role of Self–Esteem and Dispositional Affect

Abstract: Scholars have suggested that counterfactual thinking may play an important role in entrepreneurship; however, empirical research positioned to inform the nature of this relationship has been equivocal. In this study, we draw on the tenets of social cognition theory as a basis to investigate the relationship between counterfactual thinking and the dispositional attributes of the entrepreneur, hypothesizing concomitant influences upon the entrepreneur's self–efficacy. Based on a survey of 138 entrepreneurs, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
2
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 98 publications
2
62
2
12
Order By: Relevance
“…Foo et al 2009;Grichnik et al 2010) and affective traits (e.g. Arora et al 2013;. Affective states are affect generated by an external event (Baron 2008).…”
Section: Affect Mood and Emotionmentioning
confidence: 99%
“…Foo et al 2009;Grichnik et al 2010) and affective traits (e.g. Arora et al 2013;. Affective states are affect generated by an external event (Baron 2008).…”
Section: Affect Mood and Emotionmentioning
confidence: 99%
“…Extant studies into perceived self-efficacy in the entrepreneurship domain have largely focussed on either or both of two areas: first, factors that influence self-efficacy, such as counterfactual thinking (Arora, Haynie and Laurence, 2013), elements of strategic decision making processes (Forbes, 2005), business planning activities (McCann and Vroom, 2015), entrepreneurship education (Sánchez, 2013;Zhao, Seibert and Hills, 2005), pull entrepreneurship (Dalborg and Wincent, 2015), gender (Wilson, Kickul and Marlino, 2007), and national culture (Shneor, Camgöz and Karapinar, 2013). The second area focuses upon effects of selfefficacy; for example: the influence self-efficacy may have upon an individual's intention to become an entrepreneur (Bacq, Ofstein, Kickul and Gundry, 2016;Lanero, Vázquez and Aza, 2015), entrepreneurial orientation (Poon, Ainuddin and Haji Junit, 2006), and entrepreneurial passion (Dalborg and Wincent, 2015).…”
Section: Perceived Self-efficacy In the Small Business And Entreprenementioning
confidence: 99%
“…Surveys among secondary school students and university undergraduates in Malaysia revealed that self-efficacy had significant and positive relationship with entrepreneurship intention [16]- [18]. However, a study among participating US entrepreneurs revealed that cognition for self-efficacy in entrepreneurship was moderated by entrepreneurs" dispositional attributes [19].…”
Section: Introductionmentioning
confidence: 96%